C-Reactive Protein And Plasminogen Activator Inhibitor-1 A Cardiovascular Risk Predictor In Women With Polycystic Ovarian Syndrome - Ahmed Jafri, Syed Ateeq; Mir, Gh Hussain; Danaiuly, Zholdasbay Altay; Sadykov, Arman; Ahmad, Dar Mumtaz; Arzhan, Taumova; Ranjan, Himanshu (Journal of Neonatal Surgery, 2025)
Background: A diverse endocrine condition known as polycystic ovarian syndrome (PCOS) affects 6 to 10% of women of reproductive age. Menstrual irregularity, hyperandrogenism, insulin resistance, anovulatory infertility, and other endocrinopathy known as PCOS are some of its symptoms. There is mounting evidence that cardiovascular disease is becoming more common (CVD) in PCOS females. Material & method: Our study was prospective case-control research 75 healthy women were included as BMI-matched controls since they had no male-type baldness, hirsutism, acne, or hirsutism. hyperandrogenism symptoms or a family history of PCOS, as well as normal menstrual periods. Result: In present study when compared to control patients, PCOS patients had substantially higher mean blood levels of TSH, FSH, LH, PRL, hs-CRP, and PAI-1 (p 0.000). In comparison to the healthy controls, the mean fasting blood sugar was considerably higher (p 0.01). 54.16% of all patients had hs-CRP levels more than 3 mg/L, placing them at an increased risk of cardiovascular disease. Conclusion: Women with the lean phenotype of PCOS have multiple metabolic problems, including abdominal obesity, dyslipidemia, hyperandrogenemia, and insulin resistance. The conclusions of the According to the study, a milieu of continual low-grade inflammation caused by macrophage infiltration in peripheral organs exacerbates metabolic derangements and cardiovascular risk.